Catfish (Clarias gariepinus) Culture Using a Recirculating Aquaculture System: A Review of Concepts and Benefits - Ayi Yustiati; Sri Supriatinah (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Catfish farming (Clarias gariepinus) is one of the rapidly growing aquaculture sectors in Indonesia. However, the main challenges frequently encountered are limited cultivation land and declining water quality due to the accumulation of metabolic waste, particularly ammonia. The Recirculating Aquaculture System (RAS) offers a solution by reusing culture water, assisted by mechanical, chemical, and biological filtration processes. RAS aims to minimize external water exchange while maintaining water quality at levels suitable for fish survival and growth. This article aims to review the concepts and benefits of recirculating systems in catfish culture, based on a literature review of scientific journals and related books, using a descriptive-exploratory approach. The review indicates that RAS provides numerous benefits, including improved water-use efficiency, enhanced water quality, reduced ammonia concentration, and increased stocking density and productivity in catfish culture. The role of filtration units and microorganisms is crucial in maintaining system stability, particularly in the decomposition of organic waste and toxic compound